The Effect of Promotion, Perceived Price and Service Quality on Customer Decisions at Ren Coffee & Eatery - Sitti Putri Cahyani Tamsir; Efiani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of promotion, perceived price and service quality on customer decisions at Renn Coffe & Eatery. This study used a descriptive quantitative research method with 100 respondents who had visited Renn Coffe & Eatery. The type of data used in this study is primary data by collecting data using a questionnaire. The data were obtained and processed using multiple linear regression analysis supported by the IBM SPSS 22 application. The results of this study indicate that promotion, perceived price and service quality have a positive and significant influence on customer decisions at Renn Coffe.